Evaluation of Non-Cash Food Assistance Program in Improving Community Welfare in Serut Village, Panti District, Jember Regency - Masruroh, Siti Naimatul; Sunarto, Imam; Asmuni, Asmuni (Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to determine the results of the evaluation of the Non-Cash Food Assistance Program (BPNT) in improving community welfare in Serut Village, Panti District. The research method used is qualitative, which will produce descriptive data in the form of words and describe phenomena related to the program. The data collection techniques used are observation, interviews, and documentation. The number of informants used is seven people. The data analysis techniques used are data collection, data condensation, data presentation, and drawing conclusions.. The results of the study showed several criteria, namely: effectiveness in the Non-Cash Food Assistance Program (BPNT) in Serut Village, Panti District, is considered less effective because the recipients of the assistance still use old data, while the current community economy has changed. Efficiency is present because, in this case, the mechanism for receiving assistance is made flexible—aid can be taken anywhere—which makes it easier and remains within the concept of utilizing existing resources. Adequacy is achieved because the program can already meet food needs by reducing expenses. Uniformity is shown in the equal amount of assistance received by all recipients. Responsiveness is demonstrated by the good response to handling community complaints, and the Non-Cash Food Assistance Program (BPNT) implemented by the government can meet or respond to the real needs of the community.